Dampak Program GEMAR dalam Pendampingan Pemberdayaan Perempuan Rawan Sosial Ekonomi di Kelurahan Belawan Bahari Kecamatan Medan Belawan - Dedek Syahrani; Agus Suriadi (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2019)
AbstractThe purpose of this study was to find out how much the impact was felt directly and related to the positive impact of the GEMAR program in assisting the empowerment of socio-economic prone women in Belawan Bahari Village, Medan Belawan District. This type of research is descriptive research that is analyzed quantitatively. Sampling techniques using the formula N = n, the sample in this study were 30 respondents, namely women who received the benefits of the GEMAR program. This research instrument uses a questionnaire distributed to 30 respondents. The data obtained tabulated into the table is then analyzed and processed quantitative data by analysis of Case Processing Summary and Test of Normality that before and after the GEMAR program valid data amounts to 30 and no data is missing with a percentage of 100% and significance values before the program GEMAR is 0.083 and after the GEMAR program is 0.719 and greater than 0.05, the two data are declared to be normally distributed. Paired Sample Statistics analysis, Paired Samples Correlation and Paired Samples Test analysis. Based on the results of Paired Sample Statistics analysis after the GEMAR program is higher than before the GEMAR program with an average value before = 35.97 and after average value = 47.20 from 30 data, the results of Paired Samples Correlation analysis that the correlation value before and after the GEMAR program, which produces a number 0.622 with a probability value (Sig.) 0,000 that the correlation between before and after the GEMAR program relates strongly and positively, because the probability value is <0.05. Paired Samples analysis results calculated values for the impact of the GEMAR program are 7.157 with probability (Sig.) 0,000. Because the probability (Sig.) 0,000 <0,05 is rejected. This means that there is a significant influence before and after the GEMAR program in assisting the empowerment of socio-economic prone women.Keywords: Impact, GEMAR Program, Empowerment Assistance for Women in Socio-Economic Prone, Poverty AbstrakTujuan penelitian ini adalah untuk mengetahui seberapa besar dampak yang dirasakan langsung dan berkaitan dengan dampak positif program GEMAR dalam pendampingan pemberdayaan perempuan rawan sosial ekonomi di Kelurahan Belawan Bahari Kecamatan Medan Belawan. Tipe penelitian ini adalah penelitian deskriptif yang dianalisis secara kuantitatif. Jumlah sampel dalam penelitian ini adalah 30 responden yaitu perempuan yang menerima manfaat program GEMAR. Teknik pengumpulan data adalah dengan wawancara. Analisis data dilakukan analisis Case Processing Summary dan Test of Normality bahwa sebelum dan sesudah program GEMAR data yang valid berjumlah 30 dan tidak ada data yang hilang (missing) dengan persentase 100% dan nilai signifikansi sebelum program GEMAR sebesar 0,083 dan sesudah program GEMAR sebesar 0,719 dan lebih besar dari 0,05 maka kedua data dinyatakan berdistribusi normal. Analisis Paired Sample Statistics, Paired Samples Correlation dan analisis Paired Samples Test. Berdasarkan hasil analisis Paired Sample Statistics sesudah adanya program GEMAR lebih tinggi di banding sebelum ada program GEMAR dengan nilai rata-rata sebelum = 35,97 dan nilai rata-rata sesudah = 47,20 dari 30 data, hasil analisis Paired Samples Correlation bahwa nilai korelasi sebelum dan sesudah program GEMAR, yang menghasilkan angka 0,622 dengan nilai probabilitas (Sig.) 0,000 bahwa korelasi antara sebelum dan sesudah adanya program GEMAR berhubungan secara kuat dan positif, karena nilai probabilitas <0,05. Hasil analisis Paired Samples nilai t-hitung untuk dampak program GEMAR adalah 7.157 dengan probabilitas (Sig.) 0,000. Karena probabilitas (Sig.) 0,000 < 0,05 maka H₀ ditolak. Artinya terdapat pengaruh yang signifikan sebelum dan sesudah adanya program GEMAR dalam pendampingan pemberdayaan perempuan rawan sosial ekonomi. Kata Kunci: Dampak, Program GEMAR, Pendampingan Pemberdayaan Perempuan Rawan Sosial Ekonomi, Kemiskinan